2023
DOI: 10.1371/journal.pone.0279626
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of diarrhoeagenic E. coli induce enhanced monocyte and mDC responses and prevent development of symptoms after homologous rechallenge

Abstract: The experimental challenge with attenuated enterotoxigenic E. coli strain E1392/75-2A prevents diarrhea upon a secondary challenge with the same bacteria. A dose-response pilot study was performed to investigate which immunological factors are associated with this protection. Healthy subjects were inoculated with increasing E. coli doses of 1E6-1E10 CFU, and three weeks later, all participants were rechallenged with the highest dose (1E10 CFU). Gastrointestinal discomfort symptoms were recorded, and stool and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We recently demonstrated that a primary in vivo challenge of healthy volunteers with diarrheagenic E. coli bacteria strain E1392/75-2A at doses as low as 1E6 CFU resulted in protection against secondary infection three weeks later [ 27 ]. The primary infection primed monocytes and mDCs for an increased IL-6 and TNF-α production after restimulation with E. coli or TLR ligands ex vivo .…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that a primary in vivo challenge of healthy volunteers with diarrheagenic E. coli bacteria strain E1392/75-2A at doses as low as 1E6 CFU resulted in protection against secondary infection three weeks later [ 27 ]. The primary infection primed monocytes and mDCs for an increased IL-6 and TNF-α production after restimulation with E. coli or TLR ligands ex vivo .…”
Section: Discussionmentioning
confidence: 99%